2006
DOI: 10.1007/s00165-006-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

How to stop time stopping

Abstract: Zeno-timelocks constitute a challenge for the formal verification of timed automata: they are difficult to detect, and the verification of most properties (e.g., safety) is only correct for timelock-free models. Some time ago, Tripakis proposed a syntactic check on the structure of timed automata: if a certain condition (called strong non-zenoness’ SNZ) is met by all the loops in a given automaton, then zeno-timelocks are guaranteed not to occur. Checking for SNZ is efficient, and compositional (if all compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…The alternation-free restriction is not prohibitive because for any timelock-free nonzeno timed automaton (see [8]), we can express any TCTL formula into a L rel,af ν,µ MES [14].…”
Section: Timed Logic L Rel νµ and Modal Equation Systems (Mes)mentioning
confidence: 99%
“…The alternation-free restriction is not prohibitive because for any timelock-free nonzeno timed automaton (see [8]), we can express any TCTL formula into a L rel,af ν,µ MES [14].…”
Section: Timed Logic L Rel νµ and Modal Equation Systems (Mes)mentioning
confidence: 99%
“…In [34], it has been shown that every run in a timed automaton is non-Zeno if for each structural loop of the timed automaton (i.e., a loop in the timed automaton itself, not the underlying transition system), there exists a clock c such that c is reset during the loop and c is bounded from below in a guard of a transition during the loop. A weaker condition is identified in [12] (e.g., instead of checking all structural loops, only some loops are checked). Given a network of timed automata, it implies that every run is non-Zeno if the product automaton satisfies the condition.…”
Section: Introductionmentioning
confidence: 99%
“…Given a network of timed automata, it implies that every run is non-Zeno if the product automaton satisfies the condition. Sufficient conditions which guarantee absence of Zeno runs in a network without constructing the product have been identified [12]. Effectively, the work in [12] weakens the requirements imposed in [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of checking existence of Zeno runs was formulated as early as in [18]. A bulk of the literature for this problem also directs to [10,6,17]. All of these solutions provide a sufficient-only condition for the absence of Zeno runs.…”
Section: Introductionmentioning
confidence: 99%